Electrochemical performance of binder-free polyaniline based electrode for supercapacitor application / Syaza Amira Razali - Syaza Amira , Razali (2019)
This project focuses on improving the cycle stability of composite electrode consisting of conducting polymer and metal oxides. Two electrode systems were fabricated, namely polyaniline and polyaniline-nickel oxide composite (PANI and NiO-PANI) deposited on etched carbon cloth. PANI was deposited on electro-etched carbon fiber cloth by simple chronoamperometry electrodeposition method with various applied potentials. The results demonstrate that the effects of applied deposition potential significantly influence the electrochemical performance of electrodes. From the first electrode system, deposited PANI on etched carbon cloth at 1.4 V exhibited optimum specific capacitance of 357.14 F g-1. The energy density and power density was 40.18 mW h kg-1 and 1.28 W kg-1 respectively at current density of 200 mA g-1 in 0.5 M H2SO4 electrolyte. Symmetrical cell was also assembled and showed good specific capacitance retention of 88% after 2000 cycles with PVA+0.5 M H2SO4 electrolyte at current density of 200 mA g-1. In order to enhance the cycle stability and reversibility of deposited PANI on etched carbon cloth electrode, NiO was introduced by conventional heating process at different temperatures. The optimum performance of NiO-PANI on etched carbon cloth electrode was achieved when the heating temperature of 300 °C was applied. The specific capacitance obtained was 192.39 F g-1 at current density of 200 mA g-1 in 0.5 M H2SO4. The symmetrical cell employing NiO-PANI on etched carbon cloth electrode exhibited good electrochemical reversibility when discharged at different current densities over 4500 cycles. The cell was able to retain 72% of its initial specific capacitance after undergone various current density. The cell successfully restored 13.87 mW h kg-1 of its energy density after 4500 cycles. The preparation of electrodes in this work using electrodeposition method is simple, low-cost, and environmental-friendly. It holds great potential to produce cost-effective and high energy density supercapacitors.